Temperature distribution in tumour tissue during targeted destruction by heat: A hyperbolic bioheat equation approach - Mir Aijaz; Javid Gani Dar; Ibrahim M. Almanjahie; Fatimah Alshahrani (Case Studies in Thermal Engineering, 2023)
Thermotherapy is a frequently used treatment to destroy malignant tumour. The procedure is carried-out using various techniques like radio frequency, laser, focused ultrasound, and microwaves to elevate the desired temperature at targeted tissues. However, it becomes indispensable to note that the impact of the high temperatures also expands to the peripherals of the targeted tissues and can harm the surrounding healthy tissue. This paper aims to find the temperature distribution in tumour tissue during the process and draw the corresponding graphical representation. A five-tine trocar has used to raise the temperature at the centre of the targeted tissue as much as to destroy the tumour tissue. A mathematical model based on the hyperbolic bioheat equation has been formulated and solved by variable separable method after converting the devised equation into dimensionless form. The heat waves make a significant contribution in the propagation of heat at high temperatures therefore, this paper can be viewed as an improvement of the models based on parabolic Penne’s bioheat equation. The results are helpful in estimating the temperature distribution on and around the targeted tissue and hence the therapist can be guided to prevent injuries during the treatment of therapeutic treatments.